Assessment of Public Relations for Effective Healthcare Service Delivery - Remilekun Falilat Bamidele; Marie C. Obasi; Omolara Oluwabusayo Akin-Odukoya; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
Public Relations plays a critical role in shaping the reputation and operational success of healthcare organizations. Effective PR strategies ensure clear communication, foster trust, and enhance patient satisfaction. This paper assesses the role of public relations in effective healthcare service delivery, exploring its impact on patient engagement, crisis management, and institutional credibility. Healthcare institutions operate in a dynamic environment where patient trust, regulatory compliance, and public perception significantly influence their success. PR serves as a bridge between healthcare providers and the public, ensuring transparency, managing reputations, and facilitating effective communication. This study examines the role of PR in healthcare and evaluates its effectiveness in service delivery. Public Relations in healthcare plays a crucial role in patient communication and engagement by establishing clear and transparent communication with patients. It ensures that healthcare information is accurately disseminated to the public and supports patient education campaigns that improve health literacy and encourage preventive care. Additionally, PR is essential in crisis management as it helps healthcare organizations handle emergencies such as disease outbreaks, medical errors, and negative press. Effective crisis communication mitigates panic and ensures that accurate information reaches the public. The paper concludes that public relations is a fundamental tool for enhancing healthcare service delivery. By fostering trust, managing crises effectively, and ensuring clear communication, PR contributes to better patient outcomes and institutional credibility. Healthcare organizations must invest in robust PR strategies to navigate the evolving landscape of public health communication and strengthen their relationships with the communities they serve.